IgA Nephropathy: A conundrum – A case of secondary hypertension - Correia, A. (2009)
IgA nephropathy or Berger disease is an idiopathic glomerulonephritis without a well established etiology. It represents the most common cause of this entity in the world. The disease has pleomorphic presentations with confounding consequences as it happen in our case. A recurrent gross hematuria or an asymptomatic microscopic hematuria associated with mild proteinuria can give the clue for the diagnosis.Arterial hypertension in young age is another sign that can help thinking in IgA nephropathy.End-stage renal disease is the final phase of the slow progression of renal insufficiency that occurs in up to 50 percent of patients. An early diagnosis is essential to improve.